Dynamic reduced order modeling of an entrained-flow slagging gasifier using a new recirculation ratio correlation. (15th May 2017) - Sahraei, M. Hossein; Duchesne, Marc A.; Hughes, Robin W.; Ricardez-Sandoval, Luis A.
Highlights: A dynamic model is presented for CanmetENERGY's gasifier. A new empirical correlation is proposed for recirculation ratio. Transient experimental data was used to validate the model. Abstract: This study presents a dynamic reduced order model (ROM) that describes the transient behaviour of an entrained-flow slagging gasifier. A new correlation for estimation of the recirculation ratio in the ROM's reactor network is presented in this work by using the ROM and experimental data. The proposed correlation improves the well-known method of Thring and Newby for jet-flow recirculation by adding a term that takes into account the changes in the feed streams (multi-phase jet and secondary flows) on the recirculation. This feature enhances the prediction capabilities of the reactor network, especially in dynamic simulations where the inlet flowrates may change over time, e.g., for load-following power plants. The proposed dynamic ROM has been validated using steady-state and transient experimental data. Furthermore, the dynamic responses of dry syngas composition, temperature distribution, cold gas efficiency, slag thickness and flowrate were studied under load-following and co-firing (petroleum coke/coal) scenarios.